The Role of Paperless Office Systems in Supporting Office Automation Efforts: Study at One of Government Institutions in Subang District - Maya Hardiyanti; Sri Rizki; Reyisya Amelia Agina Putri; Agisni Sekar Dwi Hanggini; Abi Sopyan Febrianto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This research evaluates how local government agencies in Subang Regency implement paperless offices. The study examines the implementation, obstacles, and solutions for implementing the concept of paperless offices in government organizations. Researchers utilized a qualitative descriptive method with a case study approach. Data sources included informants, events, and documents. Data analysis involved interactive techniques, including interviews as a tool for data collection. The analysis consisted of data collection, reduction, presentation, and conclusion. The research findings indicate that implementing the paperless office system in one of the government agencies in Subang Regency aims to address issues related to paper accumulation and enhance document security through application integration. Implementing the paperless office concept can improve the efficiency of public services, enabling faster and easier processes such as application submission, reporting, and data processing.